2021
DOI: 10.3389/fmicb.2021.713408
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Molecular and Epidemiological Characterization of Influenza Viruses Circulating 2016–2020 in North Macedonia

Abstract: Influenza viruses know no boundaries, representing an example of rapid virus evolution combined with pressure exerted by the host’s immune system. Seasonal influenza causes 4–50 million symptomatic cases in the EU/EEA each year, with a global death toll reaching 650,000 deaths. That being the case, in 2014 North Macedonia introduced the sentinel surveillance in addition to the existing influenza surveillance in order to obtain more precise data on the burden of disease, circulating viruses and to implement tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…The previous literatures and surveillances of the Centers for Disease Control and Prevention (CDC) of influenza at the molecular level were mainly from immunocompetent patients [ 8 , 9 ]. With the progress of medical technology, immunosuppressed patients who have undergone haemopoietic stem cell transplantation (HSCT) or solid-organ transplantation (SOT), patients on chronic haemodialysis, and patients receiving systemic corticosteroids, immunosuppressants and biological reagents have increased each year [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%